2017
DOI: 10.3389/fmars.2017.00045
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Responses of Marine and Freshwater Photosynthetic Organisms to UVB Radiation: A Meta-Analysis

Abstract: Ultraviolet-B (UVB) radiation is a global stressor that has profound impacts on freshwater and marine ecosystems. However, an analysis of the patterns of sensitivity to UVB radiation across aquatic photosynthetic organisms has not yet been published. Here, we performed a meta-analysis on results reported in 214 studies compiled from the published literature to quantify and compare the magnitude of responses of aquatic photosynthetic organisms to changes in UVB radiation. The meta-analysis was conducted on obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 93 publications
(115 reference statements)
2
9
0
Order By: Relevance
“…Our study indicated that terrestrial organisms are the most resilient to increased UV‐B radiation, followed by freshwater and marine organisms, which is in agreement with a previous meta‐analysis that investigated UV‐B effects on photoautotrophs (Jin et al, ). Early‐life stages such as embryos and larvae are often translucent, and although many harbour photoprotective compounds, they remain particularly vulnerable to UV radiation (Aranda et al, ; Llabres et al, ; Overmans et al, ), consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our study indicated that terrestrial organisms are the most resilient to increased UV‐B radiation, followed by freshwater and marine organisms, which is in agreement with a previous meta‐analysis that investigated UV‐B effects on photoautotrophs (Jin et al, ). Early‐life stages such as embryos and larvae are often translucent, and although many harbour photoprotective compounds, they remain particularly vulnerable to UV radiation (Aranda et al, ; Llabres et al, ; Overmans et al, ), consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Although previous meta‐analyses demonstrated that the magnitude of drivers or stressors (e.g., pH change, Kroeker et al, ) or the duration of experiments (e.g., from hours to ~ 400 days, Kroeker et al, ) did not consistently explain a significant amount of variability, the magnitude of UV‐B radiation change does influence responses of marine (Llabres et al, ) and aquatic photosynthetic organisms (Jin et al, ). Our study demonstrates that the relationship between biological responses and the magnitude of temperature/UV‐B change is weak based on the whole dataset, and these overall effects vary greatly between response levels (Supporting Information Figure S2).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Therefore, to develop an experiment on interactive effects, we should consider not only the different responses of species (e.g., Roleda ) but also the origin of populations as confirmed by the meta‐analysis by Jin et al. () on the photosynthetic organism's response to UVR. Related to this, studies were carried out on the intraspecific differences in phenotypic plasticity of the macrophyte Ceratophyllum demersum (Hyldgaard and Brix ), or how the concomitant positive effect of an increase in T and N can occur depending on the charophyte population origin (Puche et al.…”
mentioning
confidence: 99%